G74 In the age of the rapid diagnostic test, are three routine blood films necessary to exclude imported malaria in children presenting to the emergency department?. (27th April 2015) - Bird, C; Jones, N; Hartshorn, S
Abstract : Aims: The number of children returning from areas endemic for malaria is increasing. Laboratory diagnosis of malaria has evolved with the advent of reliable rapid diagnostic tests (RDTs). 1 We aimed to evaluate the reliability of RDTs at one of the UK's busiest children's EDs and to assess whether this might have implications for serial testing for malaria which can be distressing to children, inconvenient for families and costly to the NHS. Methods: We audited the use of malaria RDTs (Table 1 ) ( Carestart-Malaria, Apacor ) requested in the ED over a 12-month period (October 2013–October 2014), and compared their performance against the gold standard of microscopy. Results: Population (n = 104), 48% female (n = 50), with a median age of 2.5 years. Two children were excluded from the analysis as an RDT had not been performed alongside microscopy. Most children had returned from South Asia (58%), with 18% from Sub Saharan Africa. There were no negative RDT results on preliminary testing with a positive diagnosis on microscopy. Overall, a first RDT had sensitivity of 100% and specificity of 97.8%. Of the children tested, 82% had only one RDT and blood film performed. Conclusion: In this series, a single RDT combined with one film excluded malaria in returning travellers, and this is common practice within the ED and the wider Trust. However, other studies have reported that RDTs and preliminary microscopy can rarely miss infections. 2 A larger study needs to confirm the safety of a single RDT and film. References: Abba K, Deeks JJ, Olliaro PL, et al . Rapid diagnostic tests for diagnosing uncomplicated P. falciparum malaria in endemic countries. Cochrane Library 2011. DOI: 10.1002/14651858. CD008122.pub2 Pasricha JM, Juneja S, Manitta J, et al . Is serial testing required to diagnose imported malaria in the era of rapid diagnostic tests? Am J Trop Med Hyg. 2013;88(1):20–23